Analysis of Factors That Caused Fanwar Between K-Pop Fandom on Tiktok Using Grounded Theory Analysis - Nandi Andrian Kurnia Putra; Jerry Heikal; Antoni Irawan; Zahwa Nur Syahda (Dinasti Publisher, 2024)
K-Pop is currently getting attention from various parts of the world, including Indonesia. Behind the success of K-Pop idols there are fans/fans who get in touch to support the idols they love. They will also voluntarily defend the idol they like, thereby causing feelings between fans and hurling hatred at each other. This event is commonly referred to as Fanwar on social media. Social media, especially Tiktok, is used as a place for K- Pop fans to do Fanwar. This study aims to find out which factors cause fanwar on Tiktok. This study uses a qualitative approach with a Grounded Theory approach to Coding Manual Analysis. Data were collected through interviews with 7 K-Pop fans who had seen or been involved in a fan war on TikTok. Based on the manual coding analysis conducted in this study, there were 2 themes and 8 categories. The theme obtained is that there is self-control with 5 categories, namely age, fanatic, emotion, mindset, and protect. The results of the analysis, it was found that the highest frequency of themes was in the self-control themes and the highest category was in the self-control themes, the fanatic category.